Asymmetry Matters: Structure Elucidation and Application Potential of Solution-Processed Monoalkylated BTBT Thin Films - Hawly, Tim; Johnson, Manuel; Zhao, Baolin; Wu, Mingjian; Späth, Andreas; Streller, Fabian; Nickles Jäkel, Hannah; Halik, Marcus; Spiecker, Erdmann; Watts, Benjamin; Nefedov, Alexei; Fink, Rainer (ACS Applied Electronic Materials, 2022)
Two-dimensionally (2D) extended thin films of p-type organic semiconductor C13-BTBT (BTBT = [1]benzothieno[3,2-b]-[1]benzothiophene) were fabricated via self-controlled growth at the liquid-liquid interface. Depicting a compound class originally developed for further functionalization and subsequent realization of self-assembled monolayers (SAMs), the potent BTBT core unit commonly excels in high-quality structure formation as well as charge-transport characteristics. Utilizing a manifold spectromicroscopic toolbox, we observe extraordinarily crystalline C13-BTBT films with an upright standing configuration of the backbone unit accounting for superior intermolecular orbital overlap. The well-defined morphology and internal structure of the film are being underpinned by charge-transport parameters that are in the range of comparable organic electronic devices based on bisubstituted BTBT films from the same processing technique. The inherently favorable membrane-like bilayer molecular arrangement is confirmed by unambiguous representation of the unit cell as derived from electron tomography.
CRIS-Team WoS Importer:2023-01-27

Binary cations minimize energy loss in the wide-band-gap perovskite toward efficient all-perovskite tandem solar cells - Zhang, Kaicheng; Liu, Chao; Peng, Zijian; Li, Chaohui; Tian, Jingjing; Li, Canru; García Cerrillo, José; Dong, Lirong; Streller, Fabian; Späth, Andreas; Musiienko, Artem; Englhard, Jonas; et al. (Joule, 2024)
Perovskite-based tandem solar cells stand at the forefront of photovoltaic innovation due to their exceptional performance and cost-effective fabrication. This study focuses on minimizing energy losses within a 1.80 eV perovskite sub-cell. We demonstrate that the surface treatment of perovskite with binary guanidinium bromide and 4-fluorophenylammonium iodide synergistically reduces defect densities and adjusts interfacial energy-level alignment. The enhanced passivation effect and the formation of a surface dipole significantly reduce nonradiative recombination and transport losses, leading to a notable increase in the open-circuit voltage and fill factor product, thereby achieving an impressive power conversion efficiency (PCE) of 19.0%. The reproducibility of these findings is confirmed by consistent results across different laboratories. Furthermore, integration with a narrow-band-gap perovskite yields an all-perovskite tandem device with a PCE of 27.2%. This comprehensive understanding of the pivotal role of spacer cations in surface treatment significantly advances the pathway toward efficient perovskite photovoltaics.
CRIS-Team Scopus Importer:2024-08-30
Keywords: 2D phases; all-perovskite tandem solar cell; energy loss; energy-level alignment; nonradiative recombination; passivation; spacer cations; surface dipole; surface treatment; wide band-gap perovskite

Controlling Intermediate Phase Formation to Enhance Photovoltaic Performance of Inverted FA-Based Perovskite Solar Cells - Li, Chaohui; Park, Hyoungwon; Qiu, Shudi; Streller, Fabian; Zhang, Kaicheng; Peng, Zijian; Byun, Jiwon; Tian, Jingjing; Maiti, Santanu; Xie, Zhiqiang; Dong, Lirong; Liu, Chao; et al. (ACS Energy Letters, 2024)
Formamidinium (FA)-based perovskites exhibit significant potential for highly efficient photovoltaics due to their promising optoelectronic properties and optimal bandgap. However, the undesired inactive phase arises from multiple crystal nucleation pathways formed by various intermediate phases during the film formation process, persistently accompanying it. FA-based perovskites frequently struggle to form uniform, highly crystalline films. This challenge complicates the development of reliable and highly reproducible crystallization processes for perovskites and the establishment of guidelines for controlling the α-phase formation. In this work, we investigate the role of poly(acrylonitril-co-methyl acrylate) (PAM) to simultaneously control nucleation and subsequent α-phase crystallization. This successfully demonstrates the regulation of oriented crystal growth through the creation of a PAM-PbI2 intermediate. Ultimately, PAM-modified p-i-n architecture devices obtain a promising power conversion efficiency (PCE) of 25.30%, with VOC (1.211 V), achieving 95% of the detailed balance limit. Additionally, PAM-modified devices maintain ≥90% of the initial efficiency for 1000 h under 1 sun and 65 °C operation.
CRIS-Team Scopus Importer:2024-11-22

Employing x-ray spectromicroscopy for the understanding of anisotropy in organic thin film growth - Hawly, Tim; Späth, Andreas; Johnson, Manuel; Streller, Fabian; Watts, Benjamin; Raabe, Jörg; Fink, Rainer (AIP Conference Proceedings, 2023)
We report on the fabrication of high-quality organic semiconducting thin films from the potent benchmark molecular compounds pentacene and C8-BTBT-C8. For organic films prepared by the floating-lens method, we observe 1D anisotropy in linear NEXAFS dichroism. Based on the molecular orientation contrast in scanning transmission x-ray microspectroscopy (STXM), azimuthal sample rotation and AFM, we can confirm a high degree of long-range molecular order. The experimental results allow for deeper insight into the presumed growth behavior, which appears to crucially depend on the nature, or more specifically, the aromaticity and volatility, of the used solvent.
CRIS-Team Scopus Importer:2023-12-01

Revealing Degradation Mechanisms in 3D/2D Perovskite Solar Cells under Photothermal Accelerated Ageing - Peng, Zijian; Vincze, Andrej; Streller, Fabian; Le Corre, Vincent Marc; Zhang, Kaicheng; Li, Chaohui; Tian, Jingjing; Liu, Chao; Luo, Junsheng; Zhao, Yicheng; Späth, Andreas; Fink, Rainer; et al. (Energy and Environmental Science, 2024)
Three-dimensional/two-dimensional (3D/2D) heterojunctions in perovskite solar cells exhibit excellent optoelectronic properties and enhanced stability under mild ageing conditions. However, their performance degrades drastically under harsh ageing conditions. This study reveals the intrinsic instability of mono-ammonium based 2D perovskites (2D-mono) under photo-thermal ageing, which decompose into PbI2 and metallic lead (Pb0). The structural collapse promotes vacancy formation and facilitates iodide migration to the anode. As a result, it triggers a redox reaction that reduces the transport layer’s mobility and doping concentration, leading to a significant increase in series resistance. Compared to mono-ammonium-2D structure, di-ammonium-2D (2D-di) based interfaces demonstrate superior structural stability and effectively block iodide migration into the transporting layer. However, blocking-induced uneven iodide distribution leads to interstitial defect formation in the 3D layer, exacerbating non-radiative recombination. To address it, we propose a strategical method by incorporating 2D-di in the 3D bulk instead of on the top surface, which effectively confines mobile ions within the grain and suppresses cation phase segregation. This optimization yields stable perovskite solar cells with an extrapolated operational T80 lifetime exceeding 560 hours under harsh conditions (85°C and 2-sun illumination

Tailored solution‐based N‐heterotriangulene thin films: Unravelling the self‐assembly - Hawly, Tim; Streller, Fabian; Johnson, Manuel; Miguez Lago, Sandra; Hammer, Natalie; Hampel, Frank; Vivod, Dustin; Zahn, Dirk; Kivala, Milan; Branscheid, Robert; Spiecker, Erdmann; Fink, Rainer (ChemPhysChem, 2021)
The ability of a series of bridged triarylamines, so‐called N‐heterotriangulenes, to form multilayer‐type 2D‐extended films via a solution‐based processing method was examined using complementary microscopic techniques. We found that the long‐range order, crystallinity, and layer thickness decisively depend on the nature of the substituents attached to the polycyclic backbone. Owing to their flat core unit, compounds exhibiting a carbonyl unit at the bridge position provide a superior building block as compared to thioketone‐bridged derivatives. In addition, nature and length of the peripheral substituents affect the orientation of the aromatic core unit within highly crystalline films. Hence, our results stress the significance of a suitable molecular framework and provide deeper understanding of structure formation in 2D‐confined surroundings for such compounds.<br
Keywords: bridged triarylamines; self-assembly; organic semiconductors; 2D nanomaterials; organic electronics